2017
DOI: 10.4103/jehp.jehp_154_16
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and psychological predictors of recovery from coronary artery bypass graft

Abstract: OBJECTIVES:Worldwide, i.e. in Iran, coronary artery bypass grafting (CABG) is one of the most common and expensive surgeries. This study was designed to explore the demographic and psychological factors which predict the recovery process in CABG patients.MATERIALS AND METHODS:During a prospective correlational study, 250 CABG patients, in two public and private hospitals, investigated for indexes of recovery during hospital stay and 4 weeks after discharge. Demographic and psychological variables were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(62 reference statements)
1
3
1
Order By: Relevance
“…Thus, prolonged admissions seem to lead to a feeling of less control over the heart valve disease and the subsequent recovery. These findings correspond with previous research in patients undergoing coronary artery grafting, where a reduced length of hospital stay among patients with a strong perception of control was associated with a faster recovery period 26 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, prolonged admissions seem to lead to a feeling of less control over the heart valve disease and the subsequent recovery. These findings correspond with previous research in patients undergoing coronary artery grafting, where a reduced length of hospital stay among patients with a strong perception of control was associated with a faster recovery period 26 …”
Section: Discussionsupporting
confidence: 91%
“…These findings correspond with previous research in patients undergoing coronary artery grafting, where a reduced length of hospital stay among patients with a strong perception of control was associated with a faster recovery period. 26 Patients below the age of 65 years had an increased likelihood of worse illness perception related to Consequences (of the disease). Similar findings have previously been reported in several studies as younger cardiac patients seem to perceive a significantly higher feeling of negative consequences of the disease, compared with older patients.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant difference between age and psychological status, so the psychological status was higher at the age of 31-40 years old than at other ages before the programme, while after the programme there was no relationship and all of them got better. Other studies, found that according to the logistic model, demographic variables that can influence a patient's recovery, such as age, gender, insurance, personal control over the disease, and illness perception, have a significant relationship with Bypass Graft patients (Sadeghi et al, 2017). While the findings of this study are not supported by data from another study that found no substantial relationship between age and stress (Falcoz et al, 2006).…”
Section: Discussioncontrasting
confidence: 87%
“…Other studies, found that according to the logistic model, demographic variables that can influence a patient's recovery, such as age, gender, insurance, personal control over the disease, and illness perception, have a significant relationship with various recovery products. Furthermore, it appears that these elements may be used as predictors of recovery in Coronary Artery Bypass Graft patients (Sadeghi et al, 2017 ). While the findings of this study are not supported by data from another study that found no substantial relationship between age and stress (Falcoz et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several well-documented psychosocial risk factors for cardiovascular disease [ 10 •, 11 , 12 ] are also predictors for outcomes after cardiac surgery. These factors may involve demographic variables (e.g., age and/or gender) [ 13 , 14 ], depressive symptoms [ 4 , 15 – 18 ], anxiety [ 15 , 16 , 19 21 ], chronic (work and/or family) stress [ 11 , 22 ], socioeconomic status [ 11 , 14 , 16 , 17 , 23 ], social support [ 18 ], health behaviors [ 24 26 ], marital status [ 18 ], and preoperative expectations [ 27 29 ] and illness beliefs [ 30 ]. Unfortunately, this knowledge is not sufficiently considered by current guidelines and daily routines in cardiac surgery [ 31 ••].…”
Section: Introductionmentioning
confidence: 99%